(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
The age factor plays a vital role in the perception of human beings on different issues. Regarding this, the main objective of this study is to examine the association between age group and perception of Nepali universities female teachers in the issues of women’s career success and barriers such as individual factor, family factor, organizational factor, and socio-cultural factor. With judgmental sampling technique, only 202 responses were selected and usable out of 275 questionnaires distributed to female University teachers. This study has tested the reliability by using Cronbach alpha. Using likelihood ratio, it was found that there is only a significant association of agegroup and perception of female teachers in the issue of women’s career success but there is no significant association in the issues of individual factor, family factor, organizational factor, and socio-cultural factor. From this output, it concluded that perceptions of women university teachers are different with different age-group in the issue of women’s career success. This study could be useful for University/college management, trainers, and human resource developers to assist the career success of female university teachers.